Meta-Analysis: Effects of Hormonal Contraceptive Use and History of Sexually Transmitted Disease on the Risk of Cervical Cancer - Damayanti, Siti; Budihastuti, Uki Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Cervical cancer is a sexually transmitted disease (STD) with the fourth largest number of new cases and deaths worldwide. This study aimed to analyze the effects of the use of hormonal contraception and a history of STD on the risk of cervical cancer in women. Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: women of reproductive age. Intervention: use of hormonal contraception and history of sexually transmitted infections Comparison: not using hormonal contraception and history of sexually transmitted infections Outcome: Cervical Cancer. The process of searching for articles is by searching through online journal databases which include Google Scholar, Elsevier and PubMed. With keywords “oral pill” OR “1 month injection” OR “3 month injection” OR “implant” OR “hormonal contraception” AND “cervical cancer” OR “syphilis” OR “chlamydia” OR “herpes” OR “gonorrhea” OR ”HIV” AND “Sexually transmitted infections” AND “Cross sectional” AND aOR. Articles were selected using the PRISMA flow and data analysis using the Review Manager 5.3 application. Results: This meta-analysis consisted of 12 articles from Africa and Asia . The total sample was 8,240. The use of hormonal contraception (aOR = 2.34; 95% CI= 1.83 to 4.66; p<0.001) and had history of STD (aOR = 1.97; 95% CI = 1.49 to 2.61; p<0.001) increased the risk of cervical cancer. Conclusion: The use of hormonal contraception and has history of std increase the risk of cervical cancer. Keywords: hormonal contraception, history of sexually transmitted infections, cervical cancer. Correspondence: Siti Damayanti. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami No.36, Kentingan, Jebres, Surakarta 57126, Central Java, Indonesia. Email: Sitidamayanti269@gmail.com.